Penerapan Model Pembelajaran Project Based Learning dalam Meningkatkan Hasil Belajar Matakuliah Sastra Bandingan Program Studi Pendidikan Bahasa Indonesia FKIP Universitas Bengkulu - Hiasa, Fina; Supadi, Supadi (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study aims to determine how the application of the Project Based Learning (PBL) learning model in improving learning outcomes for Comparative Literature Courses. Through the PBL learning model, students are assigned to work on pocket book project assignments. The subjects of this study were fifth semester students of the Indonesian Language Education Study Program Class A FKIP Bengkulu University who were taking Comparative Literature Courses. The research method uses classroom action research methods. Data collection techniques were carried out through oral tests and questionnaires conducted in the first and second cycles. In the second cycle the expected learning outcomes were achieved. Learning outcomes in the second cycle showed that out of 37 students there were 12 students (32%) who got an A. While the rest were students with a B grade of 20 students (54%). C grades are 5 students (14%) and D grades are 0 students (0%). These results indicate that an indicator of the successful application of the PBL model by 30% has been achieved even exceeding the 32% achievement target. In general it can be concluded that the application of PBL for Comparative Literature Courses in the University of Bengkulu University of Indonesia Language Study Program semester V of class a students of school year 2019/2020 2019/2020 can improve learning outcomes in understanding the concept of comparative literature.